Evaluation of Early Prognostic Factors of Mortality in Patients with Acute Pancreatitis: A Retrospective Study - Wenzheng Zhang; Jiang Hu; Bihui Yao; Xvsheng Yang; Lei Song; Ting Yin; Lu Liang (Gastroenterology Research and Practice)
Early and accurate assessment of severity in acute pancreatitis (AP) is of great importance to provide effective disease management and prevent mortality. In this study, we aim to evaluate early indicators that predict the mortality of AP. We retrospectively analyzed 24-hour clinical characteristics and laboratory data in 166 AP patients recruited between January 2014 and November 2015 in Baotou Central Hospital. In total, 18 patients did not survive the disease. Multivariate logistic regression showed that red cell distribution (RDW) (OR = 2.965, P=0.001) and creatinine (OR = 1.025, P=0.005) were early independent risk factors of AP mortality while albumin (OR = 0.920, P=0.032) levels reduced AP mortality. The corresponding optimal cut-off values were 14.45, 125.5, and 34.95, respectively. The positive predictive values of the AP mortality were 80.1%, 54.5%, and 69.5%. In combined measurement, the area under the curve of RDW, creatinine, and albumin was 0.964 (95% CI: 0.924 to 1.000, P<0.001). RDW ≥ 14.45%, creatinine ≥ 125.5 μmol/l, and albumin ≤ 34.95 g/l indicated a good predictive value for mortality in AP patients with a sensitivity of 100% and specificity of 64.2%. RDW, creatinine, and albumin may serve as early indicators for AP mortality which warrants further clinical investigation.